Safety and efficacy of chronic suppressive azole therapy for endemic fungal infections in solid organ transplant recipients. Issue 5 (20th July 2018) - Trinh, Sonya A.; Echenique, Ignacio A.; Penugonda, Sudhir; Angarone, Michael P.
Abstract: Background: Although the research is limited, treatment guidelines recommend lifelong suppressive azole therapy for disseminated endemic fungal infection (EFI) after solid organ transplantation (SOT). Suppressive azole therapy may prevent EFI recurrence at the risk of hepatotoxicity and drug interactions. We present real‐world safety and effectiveness data of chronic suppressive azole therapy for EFI in SOT recipients over a 10‐year period at a single comprehensive transplant center. Methods: A retrospective analysis was conducted of SOT recipients diagnosed with EFI from January 1, 2005, to May 1, 2015. Chronic suppressive azole therapy was defined as treatment for more than 12 months after diagnosis. Effectiveness of suppression was defined as preventing EFI reactivation. Safety endpoints included adverse reactions and drug interactions. Results: Over a 10‐year period, 28 SOT recipients were diagnosed with EFI: 16 histoplasmosis, 9 blastomycosis, and 3 coccidioidomycosis. Eighteen (64%) patients were treated with chronic suppressive azole therapy for a median length of 36 months (range 15‐90). One patient had an adverse drug interaction requiring azole discontinuation. There were no episodes of azole‐related hepatotoxicity, toxicity from antirejection medication, or EFI reactivation. Conclusions: Chronic suppressive azole therapy was safe and effective in preventing reactivation of EFI in SOT recipients.